2018
DOI: 10.19044/esj.2018.v14n29p36
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pastor’s Church Ministry on their Family Stability in Nairobi County, Kenya

Abstract: The family is an important place for individual mental growth. Pastors’ families, however, experience ministry related challenges with potential ramifications on their family stability. The specific objectives were; To find out the extent to which pastors work as a preacher affects family stability in selected churches in Eastlands – Nairobi County, to establish the extent to which pastoral care work affects family stability, and to determine the extent to which church administration work affects family stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Compared to manual tea picking, mechanical tea picking can improve efficiency by more than 10 times [ 47 ]. Labor on commercial tea manufacturers can represent up to 75% of the total field cost when the provision of housing and other social benefits is included [ 11 ]. Many countries including China are in the transition period from manual labor to mechanization of tea harvesting.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to manual tea picking, mechanical tea picking can improve efficiency by more than 10 times [ 47 ]. Labor on commercial tea manufacturers can represent up to 75% of the total field cost when the provision of housing and other social benefits is included [ 11 ]. Many countries including China are in the transition period from manual labor to mechanization of tea harvesting.…”
Section: Resultsmentioning
confidence: 99%
“…All these factors are without doubt important in shaping tea chemistry. However, the harvesting process itself is also important since the inappropriate collection of the leaf materials can single-handedly diminish the whole product [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Quite a number of studies that focused on marital relationships of the clergy and their partners have been conducted (Adams et al, 2017;Madukwe et al, 2019) while others have mainly targeted the clergy alone with little emphasis on the spouse and children (Guzman &Teh, 2016;Maina et al, 2018). Most of the studies have been inclined on the effectiveness of coping strategies and management of the stressors tormenting the clergy (Chan & Wong, 2018) with a few studies on the impact on children.…”
Section: Introductionmentioning
confidence: 99%
“…In developing countries, most poor households forego spending on healthcare to cater for other crucial needs such as food, thereby placing themselves at higher risks of fatalities when the diseases become untreatable [12]. Consequently, most of the poor households sink deeper into poverty as the productivity of the sick members in a family declines, coupled with low survival rate [13]. Some studies have found that, on average, approximately 75% of individuals who slide into poverty in small and medium income economies of Africa and Asia are as a result of catastrophic health spending [14,15].…”
Section: Introductionmentioning
confidence: 99%